DAMPAK ROTASI AUDITOR, SPESIALISASI AUDITOR DAN UKURAN KAP TERHADAP KUALITAS AUDIT - Ahmad Maulana (2020)
This study was conducted to examine the effect of auditor rotation variables, auditor specialization and KAP size on audit quality in the property sector and real state service companies and the infrastructure, utilities and transportation sectors listed on the Indonesia Stock Exchange (BEI) for the 2016-2019 period. The independent variables used in this study are auditor rotation, auditor specialization and KAP size. The dependent variable used in this study is audit quality. The population in this study 160 companies. The sample selection uses a purposive sampling method. Obtained a sample of 81 companies. The data obtained comes from published company financial statements. The data used in this research is secondary data. The analysis technique used is logistic regression. At a significant level of 5%. The results showed that the auditor rotation variable did not significantly influence audit quality. The auditor specialization variable and KAP size significantly influence audit quality.